The ten-year-old turbo codes are entering into service. - Berrou, C. (IEEE Communications magazine)
In the matter of channel coding and spectral efficiency, up to the invention of turbo codes, 3 dB or more stood between what the theory promised and what real systems were able to offer. This gap has now been removed, allowing communication systems to be designed with quasi-optimum performance. Ten years after the first publication on this new technique, turbo codes have commenced their practical service.